Optical Properties and Formation Mechanism of Gold Nanoparticles Fabricated by Sono-electrochemical Method - Duy Thien, Nguyen; Dinh, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics; Vol 41 No 2DO - 10.25073/2588-1124/vnumap.4763, 2025)
Gold nanoparticles (AuNPs) were synthesized rapidly by sono-electrochemical method, using gold electrodes and hexadecyltrimethylammonium bromide (CTAB) as the reducing agent. This method offers high productivity, simple equipment, and low cost. The obtained AuNPs have a size ranging from 20 to 60 nm. UV-vis absorption spectra of the synthesized AuNPs showed a peak of the surface plasmon resonance at around 530 - 548 nm, corresponding to transverse electronic oscillation. The relationship between the size of the AuNPs and their absorption spectra was investigated. Additionally, the impact of the current density, CTAB surfactant concentration, and acetone volume on the size and characteristic plasmon properties of the AuNPs was examined. The mechanism of the AuNPs formation was also discussed.